Queering Fandoms from the Periphery? A Conversation between Queer Fan Event Organizers in Mexico and the Philippines - Garza, Fen (Archīum Ateneo, 2020)
In this roundtable; I discuss with Fen Garza and James Welker the Boys Love events we have organised in the Philippines (Blush) and Mexico (Oops Summer Fest). We talk about how we've overcome the challenges of hosting a queer event for a niche audience in our countries.